Hybrid teaching (face-to-face-online) of university mathematics. A methodological proposal - Pierdant Rodríguez, Alberto Isaac; Rodríguez Franco, Jesús (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The objective of this work is to show and propose a hybrid teaching-learning methodology for university mathematics with the first experiences of an emerging educational model based on the “Guide for the return to face-to-face activities at the Autonomous Metropolitan University” (Mexico). With it, we want to prove that face-to-face and remote education offer similar learning results in mathematics. To achieve this goal, we applied a methodological proposal that combines a face-to- face math class and a video class in the ZOOM room with the support of educational material in Power Point and EXCEL. Sample size: 70 students.